Retinal Blood Vessels Extraction Based on Curvelet Transform and by Combining Bothat and Tophat Morphology - K. Gayathri; D. Narmadha; K. Thilagavathi; K. Pavithra; M. Pradeepa (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Retinal image contains vital information about the health of the sensory part of the visual system. Extracting these features is the first and most important step to analysis of retinal images for various applications of medical or human recognition. The proposed method consists of preprocessing, contrast enhancement and blood vessels extraction stages. In preprocessing, since the green channel from the coloured retinal images has the highest contrast between the subbands so the green component is selected. To uniform the brightness of image adaptive histogram equalization is used since it provides an image with a uniformed, darker background and brighter grey level of the blood vessels. Furthermore Curvelet transforms is used to enhance the contrast of an image by highlighting its edges in various scales and directions. Eventually the combination of Bothat and Tophat morpholological function followed by local thresholding is provided to classify the blood vessels. Hence the retinal blood vessels are separated from the background image.DOI:http://dx.doi.org/10.11591/ijece.v4i3.6327